2017
DOI: 10.2196/mhealth.7791
|View full text |Cite
|
Sign up to set email alerts
|

Client-Focused Security Assessment of mHealth Apps and Recommended Practices to Prevent or Mitigate Transport Security Issues

Abstract: BackgroundMobile health (mHealth) apps show a growing importance for patients and health care professionals. Apps in this category are diverse. Some display important information (ie, drug interactions), whereas others help patients to keep track of their health. However, insufficient transport security can lead to confidentiality issues for patients and medical professionals, as well as safety issues regarding data integrity. mHealth apps should therefore deploy intensified vigilance to protect their data and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
30
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(32 citation statements)
references
References 43 publications
2
30
0
Order By: Relevance
“…Although most apps did not require registration, many apps did, and they asked patients to provide self-management information without an adequate user privacy protection policy. Studies have demonstrated that many mobile medical apps are insufficiently safe [ 50 , 51 ]. Therefore, providing an adequate privacy protection policy and app security measures is critical for safeguarding users.…”
Section: Discussionmentioning
confidence: 99%
“…Although most apps did not require registration, many apps did, and they asked patients to provide self-management information without an adequate user privacy protection policy. Studies have demonstrated that many mobile medical apps are insufficiently safe [ 50 , 51 ]. Therefore, providing an adequate privacy protection policy and app security measures is critical for safeguarding users.…”
Section: Discussionmentioning
confidence: 99%
“…But mobile apps not only help the adherence to treatment; the traceability also contributes to minimizing security issues related to custody of the data and controlling the integrity of the medicine itself [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…That same study showed that 40% of the apps failed to protect the integrity of the data they displayed [91]. Other authors also expressed concerns that data integrity could be compromised as a result of attacks during transmission over public networks or simply due to immature sensor-based technology [74,75,78,80,92].…”
Section: Themes Data Transmission and Storagementioning
confidence: 99%